Effects of Commemorations and Postdonation Services on Public Willingness to Donate Bodies in China. Issue 2 (4th June 2019) - Jiang, Jingwen; Chen, Qinghuo; Zhang, Mingyi; Hong, Tongtong; Huang, Kun; Meng, Haojie; Ding, Jiong; Zhang, Luqing
Abstract : Multiple body donation programs have been established throughout China over the last 20 years, but these programs remain challenged by an insufficient supply of cadavers for medical education. The commemoration of body donors is a feature of many successful programs, and adopting this practice throughout the country could be an important element of raising public awareness and encouraging body donation among the public. The present study aimed to investigate public views on the commemoration of whole‐body donors and postdonation services in China by analyzing the factors that influence participants' willingness to donate. A survey was conducted using convenience sampling with a non‐probability sampling method, and data were analyzed using chi‐square and post hoc multiple comparisons tests. A total of 1, 800 questionnaires were distributed, 1, 717 were returned, and 1, 605 were considered valid. Of the respondents, 20.87% were willing to donate, and 64.80% thought that it is necessary to commemorate donors. The results of multiple comparisons demonstrated that the elderly and those with a higher educational level were more willing to donate than participants in other groups. Education was also found to influence views on donation memorial activities, and the chi‐square test revealed that conducting commemorations and improving postdonation services can promote the establishment of successful donor programs in China and improve the social acceptance of body donation.